2008
DOI: 10.1161/hypertensionaha.107.096552
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV in Angiotensin-Converting Enzyme Inhibitor–Associated Angioedema

Abstract: Angioedema is a potentially life-threatening adverse effect of angiotensin-converting enzyme inhibitors. Bradykinin and substance P, substrates of angiotensin-converting enzyme, increase vascular permeability and cause tissue edema in animals. Studies indicate that amino-terminal degradation of these peptides, by aminopeptidase P and dipeptidyl peptidase IV, may be impaired in individuals with angiotensin-converting enzyme inhibitor-associated angioedema. This case-control study tested the hypothesis that dipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(116 citation statements)
references
References 39 publications
3
104
0
9
Order By: Relevance
“…In addition to direct effects of bradykinin on pain, it also participates indirectly by stimulating the release of substance P from sensory nerves. 126 Furthermore, ACE also degrades substance P; 127,128 therefore, the levels of substance P are increased directly due to ACE inhibition or indirectly due to bradykinin. The nociceptive role of substance P and neurokinin 1 receptor is very well documented.…”
Section: Bradykininmentioning
confidence: 99%
“…In addition to direct effects of bradykinin on pain, it also participates indirectly by stimulating the release of substance P from sensory nerves. 126 Furthermore, ACE also degrades substance P; 127,128 therefore, the levels of substance P are increased directly due to ACE inhibition or indirectly due to bradykinin. The nociceptive role of substance P and neurokinin 1 receptor is very well documented.…”
Section: Bradykininmentioning
confidence: 99%
“…Certainly, the renal effects of DPP IV inhibitors in various patient populations merit a closer examination. In the meanwhile, it may be prudent to consider the concomitant use of an angiotensin receptor blocker or renin inhibitor (but perhaps not an angiotensin converting enzyme inhibitor which possibly could increase the risk of angioedema in patients treated with DPP IV inhibitors 19 ) in type 2 diabetics treated with DPP IV inhibitors until this issue is resolved.…”
Section: Perspectivesmentioning
confidence: 99%
“…In their article, Byrd et al 6 found that BK half-life correlated inversely with ACE activity, whether the patients received ACEIs. This important finding confirms that BK concentrations are strongly under the control of ACE expression.…”
Section: Ace Inhibition and Angioedemamentioning
confidence: 99%
“…4 On the other hand, SP is sequentially truncated by dipeptidylpeptidase IV (DP-PIV) into SP3-11 and then SP5-11, which is 1000-fold less potent than the native peptide. 5 However, the physiological importance of DPPIV in the inactivation of SP and the role of a reduction of DPPIV activity in ACEI-induced angioedema had not been evaluated before the article by Byrd et al, 6 published in this issue of Hypertension.…”
mentioning
confidence: 99%